Maine’s Artisan Cheesemakers: The Opportunities and Challenges of Being an Artist, Scientist, Agriculturalist, Alchemist, and Entrepreneur - Welcomer, Stephanie; MacRae, Jean; Davis, Brady; Searles, Jacob (Maine Policy Review, 2017)
Maine’s artisanal cheese sector has grown rapidly in the last six years. Maine cheesemakers take a variety of approaches including those based on farmsteads and operations sourcing milk from local dairies. This study examines cheesemakers’ business operations and their approaches to sustainability, opportunities, and threats. Cheesemakers report that they derive several benefits from their enterprise, but that they face challenges to ensure their long-term sustainability.
Keywords: Maine; artisanal cheese; cheesemakers; dairy